Construire des savoir-faire perceptifs en apnée - Une méthode de réflexivité en action coach-pratiquant - Schirrer, M. (Movement & Sport Sciences - Science & Motricité, 2018)
Making progress in freediving supposes in particular learning how to listen to the subtle or violent signs sent by the body. This research analyzes the difficulties and the strategies implemented by freedivers and coaches to appropriate this living body which reacts and adapts itself to the aquatic environment and to the stress generated by the situation of apnea. The conceptual framework is the one of phenomenology and sensory anthropology. The approach is an ethnographical one. The purpose of the article is double. On the one hand, reporting the activity of ordinary freedivers, from participating observations. The purpose is to identify how they learn to feel and to find their way among this diversity of physical sensations which emerge from the situation of apnea; which techniques and which procedures favor the construction of perceptive know-hows connected with physical sensations. On the other hand, presenting and analyzing a method of reflexivity in action introduced by the coach, in order to co-build, with the athlete, a sensitive scale, by characterizing the significant indications felt by the subject committed in his apnea, as well as a strategy allowing him to overtake possible hang-ups. Finally, this work is an invitation to reveal the know-hows and expertise of ground-actors committed to improve some perceptive processes, in the service of improved performances and/or of a better management of his physical capital.